Analysis of Economic Digitalization of IKM Pande Besi as Supporting Strategies for Developing Product Marketing Intensity - Kristanti, Bella Arum; Hariyani, Tuwis; Sari, Rini Ratna Nafita (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The aim of the research is to determine the influence of modern technology consisting of the use of smartphones and digital marketing on increasing marketing of iron pande products. Design/Method/Approach: The type of research in this research is Quantitative Method. This data collection was carried out using research instruments in the form of interviews and questionnaires as the main data sources, and secondary data sources were also used to complete the research. The analysis used in this research uses Binnary Logistic Regression Analysis. Research Finding: Gadget ownership, digital marketing and price factors influence the marketing intensity of Pande Besi SMEs. The digital economy is a new challenge that is being faced by business actors, including SMEs. Therefore, SMEs must be able and ready to run their businesses using the digital economy concept.